The Social Criticism on the Anthology of Poetry Portrait of Development by WS Rendra - Lestari, Sri Indah; Alfiawati, Riska; Sudarmaji, Sudarmaji (IJLHE: International Journal of Language, Humanities, and Education, 2018)
This study aims to describe social criticism in the poetry anthology "Portrait of Development" by W.S. Rendra. The social criticism studied includes social criticism of life, economic criticism, political criticism, and moral criticism. The research method uses qualitative. The primary data source in this research is the poetry anthology "Portrait of Development" by W.S. Rendra. Data collection techniques that will be used are documentation and observation. Data analysis using document content analysis. The results showed social criticism in the collection of poems "Portrait of Development" by WS. Rendra. The social critique of life is found in the poems "The Poems of the Poor" and "Jockey Tobing's Poem for Widuri," as well as in the poem "The Poem of A Corn." WS Rendra conveyed economic criticism in the poems "The Poems of the Poor" and "The Poems of the Condor Birds", "The Sun Poem", "The Poem of A Corn", and the poems "The Poem of an Old Man Under the Tree." WS Rendra conveyed political criticism in the poem "Young Children's Poems" and "Spouses of Spying". WS Rendra conveyed moral criticism in the poems "Poor People's Poems" and "Young Children's Poems", "Spouses of Spying", "The Poem of A Corn", and "The Poem of An Old Man Under a Tree."